RANCANG BANGUN APLIKASI PENDAFTARAN PASIEN ONLINE DAN PEMERIKSAAN DOKTER DI KLINIK PENGOBATAN BERBASIS WEB - Andi Suprianto (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2021)
The purpose of this web-based application design is to facilitate the patient in registering himself or his family members without having patients waiting in line and waiting long. Facilitate clinic staff in serving patient registration. Increase time efficiency in patient service. Facilitate the patient in knowing the results of medical record, So that patients can know the disease that is attacking the immune system. Facilitate medical clinical administration staff in preparing reports without having to expend large costs. In this case, web-based applications are the right choice, because the operating system is online. The research method is to collect data through observation in Medical Clinic. Then spread the questionnaires and interviews. This application is built using PHP application program and using MySQL database. The results of the design of the application of online patient registration and doctor examination is expected to help Admin (administrative staff) and user (patient) by utilizing internet connection. Keywords: Patient Registration, Medical Examination, Medical Clinic, PHP, Mysql